The Effect of Work Motivation and Work Discipline on Employee Performance at Gojek Manado Office - Laminullah, Pratiwi Rizka; Luturlean, Bacharuddin Saleh (Jurnal Ilmiah Sumber Daya Manusia, 2023)
Work motivation can create a positive work atmosphere full of enthusiasm at work so that it makes it easier to achieve goals and creates an attitude to be disciplined in complying with applicable rules. Regulations are needed to provide good work discipline, employee work efficiency and can provide high motivation to employees. Performance has an important role because performance is the final form of the process of employees completing their tasks. Employees who complete their duties properly and correctly will have high performance. The purpose of this study was to determine the effect of work motivation and work discipline on employee performance at the Manado Gojek Office, either partially or simultaneously. This type of research uses quantitative research using a descriptive observational research design. This research uses probability sampling technique. This study uses data analysis techniques using the classical assumption test statistical method, Multiple Linear Regression Test and hypothesis testing.